PLANT EXTRACTS AS CORROSION INHIBITORS FOR ALUMINUM ALLOY IN NACL ENVIRONMENT - RECENT REVIEW - lavanya; Preethi Kumari (Journal of the Chilean Chemical Society, 2022)
In spite of the fact that aluminium and its combinations are regularly used like lightweight materials in a great deal of enterprises, they experience the ill effects of low erosion resistance. Corrosion is a natural phenomena that leads to the deterioration of the metal properties through its electrochemical interaction with the corrosive environment. The costs related to corrosion can be either direct (due to the replacement and maintenance) or indirect. A few strategies and methods have been utilized to mitigate corrosion in aluminium and its compounds under various conditions. Concerns raised over climate and human wellbeing have constrained industries to search for a more appropriate option for the protection of aluminium and its alloys from corrosion. This review emphasizes on the plant extracts applied for aluminium combination consumption restraint in NaCl medium. It summarizes the different techniques used for extraction. Additionally, an understanding to the adsorption isotherms has been discussed in brief.